Incidencia de cáncer en el Instituto del Seguro Social, seccional Antioquia 1987-1992 (1996)
ABSTRACT: The authors show some aspects of the registered cancer incidence in the Instituto de Seguros Sociales, in the Antioquia region, Colombia, for the periods 1987-1990 and 1992, and for a population of workers and their families. The average annual incidence rates are presented by site, age and sex, and such rates compared with those reported for the period 1968-1972. A higher incidence among women is observed for tumors of stomach and larynx (among women older than 50 years of age), lung over (older than 35), and breast and uterine cervix (over 45). The lowest incidence of ovarian tumors was shown for women younger than 50 years. Also the age-adjusted incidence rates of selected sites are compared with those reported by the population based registry of Cali, Colombia and the main differences are presented.